THE IMPACT OF EMPLOYEE ENGAGEMENT ON ORGANIZATIONAL CULTURE AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE - Puspita Dewi Mayangsari; Furtasan Ali Yusuf; Ade Manggala Hardianto (International Journal of Economy, Education and Entrepreneurship, 2022)
The Research aims are to measure performance by the achievement or success of employees in carrying out their duties and the parameters of the success of achieving targets. Finally, this paradigm can build organizational progress if the organization has cultivated a standard order, values, and commitment. This research method uses analysis of the measurement method (outer model) to determine whether the measurement can use to show valid and reliable information. Convergent validity, discriminant validity, and composite reliability are indicators of the outer model analysis in this study. The study results explain that almost all positive hypotheses are significant, except for the third hypothesis, with a p-value of 0.263> 0.05, and the sixth hypothesis, P values of 0.0275> 0.05